THE IMPACT OF FOREIGN DIRECT INVESTMENTS ON ECONOMIC GROWTH AND INTERNATIONAL TRADE: THE EXAMPLE OF E7 COUNTRIES (Third Sector Social Economic Review, 2025)
In recent years, empirical studies investigating the relationship between foreign direct investment and its effects on international trade and economic growth have become increasingly popular. Foreign direct investments and international trade are at the heart of ensuring continuous economic growth. Hence, this study emphasizes further investigation of the relationship between FDI, economic growth, and international trade. For this study, E7 (Turkey, Mexico, Indonesia, China, Brazil, Russia, India) countries have been taken into consideration. The research was undertaken using a panel data analysis from the 1992-2022 dataset. The results of the study reveal that FDI economic growth and international trade cointegrate. The AMG estimation applied in this study indicates that there is a significant and positive import-foreign direct investment relationship among all other international trade indicators. Nevertheless, the results show that FDI inflows result in diversification in export structures, which creates resiliency for the economy in E7 countries. It was also found that where trade openness is very large in a country, then FDI would be affine, further increasing the potential for economic growth. The analysis indicates that policy reforms that improve conditions for investment and introduce trade liberalization would be effective in supporting such positive effects. These show what E7 will do economically sustainably in the long term—devise strategies to strengthen the FDI-intraconnect trade link.
Keywords: International Trade; Economic Growth; Foreign Direct Investment; Panel Data; E7 Countries